2000
DOI: 10.1051/agro:2000138
|View full text |Cite
|
Sign up to set email alerts
|

The absence of the short arm of chromosome 7B produces inhibition of N mobilization and decreases grain protein concentration in wheat (Triticum aestivum L.) cv. Chinese Spring

Abstract: The ditelosomic line CSDT7BL of wheat (Triticum aestivum L.) cv. Chinese Spring (CS), in which the short arm of chromosome 7B is missing, has been described as accumulating less protein in the grain than the normal line. In the present paper, we studied the protein accumulation and N mobilization in CSDT7BL and CS grown in the field under two N fertilization regimes, over two successive years in field-grown plants. The N treatments applied as urea were 0 or 300 kg N/ha in the first year, and 0 or 200 kg N/ha w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It has been observed that the efficiency of N remobilization is governed by the availability of N in the soil. That is, N remobilization efficiency decreases with the increase in N availability (Dalling 1985, Fatta et al 2000, Ercoli et al 2008. Furthermore, an increase in the phloem amino acid exudation rate at the beginning of the grain filling period has been observed in field-grown barley plants subject to N deficiency (Veliz et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the efficiency of N remobilization is governed by the availability of N in the soil. That is, N remobilization efficiency decreases with the increase in N availability (Dalling 1985, Fatta et al 2000, Ercoli et al 2008. Furthermore, an increase in the phloem amino acid exudation rate at the beginning of the grain filling period has been observed in field-grown barley plants subject to N deficiency (Veliz et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Final N concentration depends on soil NO 3 − absorbed and reduced during grain filling and on the remobilization from source tissues of N accumulated during vegetative period. Under conditions of high N availability in the soil, remobilization efficiency is decreased and a significant amount of N remains in the straw after harvest (Dalling 1985;Fatta et al 2000;Ercoli et al 2008). Barley, besides its importance as a crop, is an established model plant for agronomic, genetic, and physiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…In common wheat, a number of QTL in chromosomes with which "direct" use of nitrogen for grain filling is associated are identified (1A, 4A, 1D) [65]. It was demonstrated on populations of T. durum from the cross DT695/Strongfield that an increase in GPC in recombinants is associated with the contribution of two main QTL both in N remobilization (on 2BL) and in direct intake of N into grain (on 7AL) [50].…”
Section: Remobilization Of Nitrogenmentioning
confidence: 99%